Degree and types of domestic abuse in the elderly referring to - Manoochehri, H; Ghorbi, B; Hosseini, M; Nasiri Oskuyee, N; Karbakhsh, M (Advances in Nursing & Midwifery, 2009)
Background Aging has always been concerned throughout history. The second half of the 20th century has been referred as population graying due to increased number of elderly people. Of related familial and social outcomes is the upsurge of antisocial behaviors and violence. Domestic elder mistreatment or abuse as a major health problem is a type of familial violence with a significantly increasing incidence in the last 2 decades. Since there is no specific organization to be responsible for this problem in developing countries like Iran, no information or evidence is available and limited studies are only limited to developed countries. Purpose This descriptive study was conducted to determine the degree and types of domestic abuse in the elderly referring to parks of Tehran. Methods 400 elders 60 years and over including men and women from all parts of Tehran took part in the study. A questionnaire in 3 parts including demographics, types of abuse and open questions was used for data collection. The tool was validated by face and content methods and made reliable by internal consistency as well as test-retest methods. The questionnaire was completed by the researcher through interviewing the subjects. Results Findings showed that 28% of the elderly was between 70 and 74, 38.2% had secondary education, 65.1% was married and 32.9% lived with their spouses. 87.8% of them experienced at least 1 type of abuse, 12.2% no abuse and 24.9% all 4 types of abuse. 84.8% experienced emotional abuse; 68.3%, neglect; 40.1%, financial exploitation; and 35.2%, physical abuse. A positive correlation was found between age and abuse. In contrast, no relationship was found between abuse and sex, educational level, marital status, living condition as well as geographic area. Conclusion It can be concluded that domestic abuse is a widespread social problem which requires urgent, continuous and fundamental interventions. Clarification of the issue from different aspects, identification of predisposing and preventive factors and recognition of at-risk elderly are of high priorities in this regard. Keywords: Elderly, Domestic abuse, Parks.